2013
DOI: 10.3109/00365521.2013.832365
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological investigation of lymph node metastasis predictors in superficial esophageal squamous cell carcinoma with a focus on evaluation of lympho-vascular invasion

Abstract: OBJECTIVE. Reliable indicators of the risk of lymph node metastasis (LNM) in superficial esophageal squamous cell carcinoma (sESCC: intramucosal and submucosal invasive carcinoma) may contribute to assist optimal clinical decision-making for treating sESCC. In esophageal cancer, there is a possibility of metastasis, even in sESCC, and careful evaluation is needed when making a pathological diagnosis. In this study, we objectively evaluated predictive factors of LNM. MATERIALS AND METHODS. A total of 110 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…This might be attributable to the small number of cancer‐related deaths and/or recurrences (especially in single‐institution cohorts) among patients with such small cancers. It is of note that five studies (Teramoto et al ., Nakagawa et al ., Landau et al ., Ito et al ., and Mitobe et al …”
Section: Discussionmentioning
confidence: 97%
“…This might be attributable to the small number of cancer‐related deaths and/or recurrences (especially in single‐institution cohorts) among patients with such small cancers. It is of note that five studies (Teramoto et al ., Nakagawa et al ., Landau et al ., Ito et al ., and Mitobe et al …”
Section: Discussionmentioning
confidence: 97%
“…Other features have been found to be prognostic assessment of patients with ESCC. In this regard, the presence of tumor size, differentiation, location, performance status of patient, tumor infiltration depth, lymph node status and distant metastasis have a major role, and are extensively utilized in clinical setting [4], [10][11], [14], [17]–[23].…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Kitagawa et al investigated the prognostic value of epidermal growth factor receptor (EGFR) gene amplification in patients with ESCC and found that vascular invasion was proved to retain independent prognostic value [12]. Importantly, vascular invasion in superficial ESCC is also found to be a strong independent predictor of lymph node metastasis with an odds ratio of 12.01 [14]. Notably other published reports show no significantly prognostic value for vascular invasion to predict the outcome in patients with ESCC [15]–[16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not defined either dominant histopathological grade or the highest grade should be adopted. Although I admit that histopathological grading surely has close relation to the probability of lymph node involvement in T1a-MM and T1b tumors, more detailed discussion is necessary on this issue (20)(21)(22). Though this grouping would have been defined so that the prognoses can be properly stratified, it should be database-restricted, and i.e., therapeutic measurerestricted.…”
Section: Pathological Prognostic Groupmentioning
confidence: 99%